Optimization of the Police Goes to Factory Program by the Dikyasa Traffic Unit to Private Employees in Reducing the Number of Traffic Violations in the Jurisdiction of the Cianjur Police - Putra, Hendon Hanif (Police Studies Review, 2024)
The traffic situation in Cianjur Regency is quite heavy due to factory activities located on the side of the protocol road, triggering traffic congestion that allows traffic accidents on the highway. Kamseltibcar lantas in the jurisdiction of the Cianjur District Police was still not created properly. Therefore, need for awareness and understanding of the community, especially those who work as private employees. Police prevention efforts have been carried out in handling traffic violations through community education programs about traffic or called Dikmas Lantas. The purpose of this study is to describe, analyze the implementation of the program also the influence factor of the Police Goes to Factory program and explain how the program optimizes the unit in reducing the number of traffic violations to the people in the Cianjur district police jurisdiction. This type of research is a qualitative research with descriptive analysis research. The location of this research is in the Cianjur district police jurisdiction where private employees are the object of this study. Data was collected by observation, interview and document study and analyzed by reducing data, presenting it and drawing conclusions. The results showed that there were some shortcomings during implementation, namely the quality and quantity of personnel, activity budgets and lack of activity implementation intensity. The factors that influence the implementation of the unit are human, money, completeness, market and method. To optimize the community education program, the qualifications of personnel abilities need to be analyzed using performance theory, namely capability, clarity, support, motivation, validity and environment.